Pengembangan Kapasitas Pembudidaya Ikan Melalui Pemanfaatan Maggot Sebagai Pakan Alternatif Di Kota Parepare - Suherman; Kadir, Muhammad Jurhadi; Mutmainnah, Nurul; Zulfiani (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2024)
Purpose – This community service activity aims to increase the knowledge and skills of small fish farmers in Parepare City in adopting maggots as an effective and affordable alternative feed. In addition, reducing dependence on expensive commercial feed will provide significant economic benefits for fish farmers and positively affect environmental sustainability. Design/methodology/approach – The method includes identifying target groups for small-scale tilapia and catfish farmers, as well as training and workshops on maggot cultivation techniques and their use as fish feed. Technical assistance is provided to ensure efficient and environmentally friendly maggot production practices, focusing on using household and market waste as raw materials. Findings – The results of this activity show a significant increase in farmers' understanding of feed diversification and reduced production costs. The participants succeeded in applying maggot-rearing techniques using the stacked bucket method and managing organic waste for maggot production. Participant evaluation revealed that 82% had knowledge of the potential of maggots as an alternative feed, and 100% understood black fly breeding techniques for maggot production. Originality/value – Using maggots from organic waste supports more sustainable fish farming practices, reduces the carbon footprint by utilizing organic household or market waste, and helps overcome waste management problems in Parepare City.